Impact of Metformin Use on Esophageal Cancer Recurrence and Survival: A Systematic Review and Meta-Analysis: 369 - Wilder, Evan; Poles, Jillian; Yang, Brooke; Popov, Violeta (The American journal of gastroenterology, 2018)
Introduction: Esophageal cancer (EC) has a poor prognosis, and a growing body of work has suggested links to modifiable metabolic risk factors such as obesity and diabetes. Metformin, a commonly used medication to treat obesity and diabetes, is a known activator of AMP kinase, and can stabilize p53. It has been shown to slow EC growth in rodents. We hypothesized that use of metformin may have an impact on EC survival and incidence in humans. To assess this, the effect of metformin use on EC was explored in a systematic review and meta-analysis of published human studies. Methods: A systematic search was conducted in PubMed, EMBASE, and Cochrane CENTRAL. Search terms included subject headings and keywords for the concepts of esophageal neoplasms and metformin. Inclusion criteria were retrospective and prospective cohort studies reporting EC outcomes of at least 1 month after cancer with at least 5 adult patients. Primary outcomes included 2 and 5-year overall survival (OS) and disease free survival (DFS) and secondary outcomes included complete pathologic response (CPR). Risk ratios (RR), and 95% confidence intervals (95% CI) are reported. Random effects analysis was performed for all outcomes, with heterogeneity assessed by the I2 statistic. Results: 134 total citations were identified, and 4 articles comprising of 2,116 subjects, were ultimately analyzed, all retrospective cohort studies. The average follow-up time was 5 years, range 1-228 months. In three of the four studies, all patients had underwent chemoradiation therapy (96% in the fourth). In two of the studies > 40% of patients had also received esophagectomy. Metformin use was associated with improved two-year disease free survival, RR 0.77 (95% CI 0.65, 0.92), p=0.005, I2= 0%, improved two year overall survival, RR 0.67 (95% CI 0.54, 0.85), p=0.001, I2=0%; and improved five year overall survival, RR 0.56 (95% CI 0.41, 0.77), p=0.001, I2=0%. Additionally, the likelihood of CPR was greater in metformin users, RR 0.67 (0.47, 0.96), p=0.03, I2=0% Conclusion: Metformin use was associated with increased disease free survival and response to therapy. Of note, this effect was present even after individual studies accounted for other variables known to affect treatment response, as well as noted dose dependent effect, with higher doses of metformin linked to improved response. Further prospective studies examining this promising effect of metformin are warranted.